An Analytical Solution for the Dynamics of a Functionally Graded Plate resting on Viscoelastic Foundation - Thuy, Dang Thu; Nguyen Ngoc, Lam; Tien, Dao Ngoc; Thanh, Hoang Van (Engineering, Technology & Applied Science Research, 2023)
This paper deals with the dynamic response of Functionally Graded Material (FGM) plates resting on a viscoelastic foundation under dynamic loads. The governing equations are derived by using Hamilton’s principle using the classical plate theory and the higher-order shear deformation plate theory. Using state-space methods to find the closed-form solution of the dynamic response of functionally graded rectangular plates resting on a viscoelastic foundation. Numerical examples are given for displacement and stresses in the plates with various structural parameters and the effects of these parameters are discussed. The result of the numerical example shows a marked decrease in displacement and stresses as the coefficient of viscous damping is increased.